Mechanical analysis of a Solar Array hinge based on a 180∘ folded flexible printed circuit board - Bartsch, F. Yves; Seefeldt, Patric; Wippermann, Torben; Reershemius, Siebo (Acta astronautica, 2022)
Flexible Printed Circuit Boards (Flex PCB) are commonly used for the electrical routing on spacecrafts (S/C). The implementation of Flex PCB as structural material and harness for the Gossamer Solar Array (GoSolAr) is currently studied by the German Aerospace Center (DLR). The Flex PCB as well as the other parts of the array are folded and stowed into a small volume for transport into space and deployed once the spacecraft starts operating. The folding areas, also referred to as hinge, are subject of this paper. The hinges and their design have major impact on the required deployment force and geometry. The aim is to get a better understanding of the relevant parameters, which are the deployment force, the angles between photovoltaic generators and the deployed distance. Deployment experiments were carried out on four different design options, which were then compared to each other with respect to their deployment behaviour. Important aspects for this evaluation were the controllability during the deployment and the force required for tensioning the array. Main differences of the evaluated designs were the amount of elastic deformation energy stored in the different configurations (stowed and deployed). The experiments revealed that a design, which has its minimum of elastic deformation energy in stowed configuration is beneficial to be used for GoSolAr. Furthermore, a numerical model of the hinge based on the FEM is introduced. The experiments were used to correlate the model. This model can be further used for design studies and optimization. The design of Flex PCB as hinges adds a mechanical function to its otherwise only electrical purpose and therefore opens a whole new field of applications, especially for thin film and lightweight structures. •Flexible Printed Circuit Boards (Flex PCB) can actively be used as mechanical hinge.•Advantageous for lightweight and thin film structures.•The overall hinge performance depends on how and when the elastic energy is stored.•Minimum of elastic energy in stowed configuration turned out to be most beneficial.•Maximum of elastic energy at the end of deployment increases controllability.